Pleural effusions in hematologic malignancies and their management with indwelling pleural catheters. Issue 4 (July 2018) - Vakil, Erik; Jimenez, Carlos A.; Faiz, Saadia A.
Abstract : Purpose of review: Pleural effusions in patients with hematologic malignancy may represent malignant pleural effusion (MPE) or occur secondary to infection, treatment effects, and other common causes. The impact of MPE on prognosis in this cohort remains unclear. Indwelling pleural catheters (IPCs) are routinely placed for palliation of recurrent symptomatic MPEs, but perceived concerns over infection and bleeding may limit their use in patients with hematologic malignancies. However, recent evidence suggests IPCs are both well tolerated and effective in this cohort. In this review, the evaluation of pleural effusions in hematologic malignancies and their management with an IPC are outlined. Recent findings: Two retrospective studies have been published regarding the use of IPCs in hematologic malignancies. Lymphomatous effusions are the most common cause of MPE in this cohort. The rates of complications and pleurodesis with IPC in hematologic malignancies are similar to those with solid organ tumors. Summary: Pleural effusions in patients with hematologic malignancies may be managed safely with an IPC. Sterile technique, barrier protection, standardized algorithms for placement and removal, and quality assurance initiatives are crucial to centers that place IPCs for all patients. The safety of IPC in hematologic malignancies warrants a paradigm shift in the management of pleural disease for this cohort.